Palladium-Catalyzed Direct Functionalization of Imidazolinone: Synthesis of Dibromophakellstatin - Lu, Jianming (2007)
[Image: see text] The direct C-H functionalization of imidazolinone is achieved with Pd(OAc)(2)/NaOAc in DMSO. Dibromophakellstatin can be synthesized in 5 steps with 40% overall yield using this new C-H activation method.